The Effect of Business Capital and Business Duration on Business Income: Digital Accounting as a Moderating Variable - Putri, Nurapni Jami (The Future of Education Journal, 2024)
This study aims to explore the effects of business capital and business duration on business revenue, with digital accounting as a moderating variable. The research employs a quantitative survey approach and was conducted with a sample of 70 small and medium-sized enterprises (SMEs) in Sungai Penuh, Jambi Province. The findings of the study reveal that both business capital and business duration have a significant and positive influence on business revenue, together explaining 40.1% of the variance in revenue. This suggests that businesses with higher capital and longer operational durations tend to generate more revenue. However, the study also found that digital accounting does not have a significant moderating effect on the relationship between business capital, business duration, and revenue, despite the fact that its inclusion in the analysis increased the explanatory power from 40.1% to 63.1%. This indicates that while digital accounting has the potential to improve understanding of business performance, its impact in moderating the relationship between traditional business factors (such as capital and duration) and revenue is still limited. The results suggest that traditional factors, such as adequate capital and business longevity, play a more direct and influential role in driving revenue compared to the current role of digital accounting tools. This highlights the need for SMEs to focus on strengthening foundational business elements, but also indicates that the integration of digital accounting could provide additional insights into business operations and potentially improve business outcomes over time, although its effects are not yet pronounced in this context.